A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China) - Gyulai, Peter; Saldaitis, Aidas; Zilli, Alberto (Zootaxa, 2019)
A new genus of Apameini (Noctuidae) from Western Sichuan, China, Alena gen. n. with a single species (Alena alena sp. n.), are described. The new species is strikingly similar in habitus to several unrelated Noctuidae.